Outcomes after definitive surgery for mandibular osteoradionecrosis. Issue 6 (3rd March 2022) - Contrera, Kevin J.; Chinn, Steven B.; Weber, Randal S.; Roberts, Dianna; Myers, Jeffery N.; Lai, Stephen Y.; Lewis, Carol M.; Hessel, Amy C.; Gillenwater, Ann M.; Mulcahy, Collin F.; Yu, Peirong; Hanasono, Matthew M.; et al.
Abstract: Objectives: To analyze charges, complications, survival, and functional outcomes for definitive surgery of mandibular osteoradionecrosis (ORN). Materials and Methods: Retrospective analysis of 76 patients who underwent segmental mandibulectomy with reconstruction from 2000 to 2009. Results: Complications occurred in 49 (65%) patients and were associated with preoperative drainage (odds ratio [OR] 4.40, 95% confidence interval [CI] 1.01–19.27). The adjusted median charge was $343 000, and higher charges were associated with double flap reconstruction (OR 8.15, 95% CI 2.19–30.29) and smoking (OR 5.91, 95% CI 1.69–20.72). Improved swallow was associated with age <67 years (OR 3.76, 95% CI 1.16–12.17) and preoperative swallow (OR 3.42, 95% CI 1.23–9.51). Five‐year ORN‐recurrence‐free survival was 93% while overall survival was 63% and associated with pulmonary disease (HR [hazard ratio] 3.57, 95% CI 1.43–8.94). Conclusions: Although recurrence of ORN is rare, surgical complications are common and charges are high. Poorer outcomes and higher charges are associated with preoperative factors.